Предмет: Математика,
автор: Аноним
10:(2 12/17+1 5/17)-(3 4/5+1 3/5):6
Ответы
Автор ответа:
4
10 ÷ (2 12/17 + 1 5/17) - (3 4/5 + 1 3/5) ÷ 6 =1 3/5 = 1.6
2 12/17 + 1 5/17 = 46/17 + 22/17 = (46 + 22)/17 = 68/17 = 4
10 ÷ 4 = 10 × 1/4 = 5/2 = 2 1/2
3 4/5 + 1 3/5 = 19/5 + 8/5 = (19 + 8)/5 = 27/5 = 5 2/5
5 2/5 ÷ 6 = 27/5 ÷ 6 = 27/5 × 1/6 = 9/10
2 1/2 - 9/10 = 5/2 - 9/10 = 25/10 - 9/10 = 16/10 = 8/5 = 1 3/5
1 3/5 = 1.6
2 12/17 + 1 5/17 = 46/17 + 22/17 = (46 + 22)/17 = 68/17 = 4
10 ÷ 4 = 10 × 1/4 = 5/2 = 2 1/2
3 4/5 + 1 3/5 = 19/5 + 8/5 = (19 + 8)/5 = 27/5 = 5 2/5
5 2/5 ÷ 6 = 27/5 ÷ 6 = 27/5 × 1/6 = 9/10
2 1/2 - 9/10 = 5/2 - 9/10 = 25/10 - 9/10 = 16/10 = 8/5 = 1 3/5
1 3/5 = 1.6
Nastya171167:
да по действиям
Автор ответа:
0
10:4-5 2/5:6=2.5-0.9=1.6
Похожие вопросы
Предмет: Русский язык,
автор: vasya8800
Предмет: Українська мова,
автор: Lera0075
Предмет: Русский язык,
автор: VeraMonik
Предмет: Химия,
автор: victoriagolubeva79
Предмет: Английский язык,
автор: luizagoryachki